Auditory stimuli elicit hippocampal neuronal responses during sleep - Vinnik, Ekaterina; Antopolskiy, Sergey; Itskov, Pavel M.; Diamond, Mathew E. (Frontiers in Systems Neuroscience, 2012)
To investigate how hippocampal neurons code behaviorally salient stimuli, we recorded from neurons in the CA1 region of hippocampus in rats while they learned to associate the presence of sound with water reward. Rats learned to alternate between two reward ports at which, in 50 percent of the trials, sound stimuli were presented followed by water reward after a 3-second delay. Sound at the water port predicted subsequent reward delivery in 100 percent of the trials and the absence of sound predicted reward omission. During this task, 40% of recorded neurons fired differently according to which of the 2 reward ports the rat was visiting. A smaller fraction of neurons demonstrated onset response to sound/nosepoke (19%) and reward delivery (24%). When the sounds were played during passive wakefulness, 8% of neurons responded with short latency onset responses; 25% of neurons responded to sounds when they were played during sleep. Based on the current findings and the results of previous experiments we propose the existence of two types of hippocampal neuronal responses to sounds: sound-onset responses with very short latency and longer-lasting sound-specific responses that are likely to be present when the animal is actively engaged in the task. During sleep the short-latency responses in hippocampus are intermingled with sustained activity which in the current experiment was detected for 1-2 seconds.